2019
DOI: 10.1021/acsnano.9b00587
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stress-Dependent Autophagy Component Release via Extracellular Nanovesicles in Tumor Cells

Abstract: Tumor cells metastasizing through the bloodstream or lymphatic systems must withstand acute shear stress (ASS). Autophagy is a cell survival mechanism that functions in response to stressful conditions, but also contributes to cell death or apoptosis. We predicted that a compensation pathway to autophagy exists in tumor cells subjected to mechanical stress. We found that ASS promoted autophagosome (AP) accumulation and induced release of extracellular nanovesicles (EVs) containing autophagy components. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 59 publications
2
42
0
Order By: Relevance
“…To investigate whether this response was lysosomal-dependent, knockdown of SNARE STX17 was performed to inhibit lysosomal fusion, but no effect on EA was seen, indicating a strict endosomal response (Mejlvang et al 2018). The existence of a rapid autophagy response to cellular stress was further demonstrated by Wang et al (2019). By applying mechanical stress to tumor cells for up to 60 min., increases in LC3II and p62 was seen in the EV fraction.…”
Section: Endosomal Autophagymentioning
confidence: 99%
“…To investigate whether this response was lysosomal-dependent, knockdown of SNARE STX17 was performed to inhibit lysosomal fusion, but no effect on EA was seen, indicating a strict endosomal response (Mejlvang et al 2018). The existence of a rapid autophagy response to cellular stress was further demonstrated by Wang et al (2019). By applying mechanical stress to tumor cells for up to 60 min., increases in LC3II and p62 was seen in the EV fraction.…”
Section: Endosomal Autophagymentioning
confidence: 99%
“…Similar with numerous early studies accumulations of autophagic vesicles in HCQ treated cells have already been observed in our experiment. [38] It has remained unclear whether this phenomenon was due to an inhibition of fusion or a block in lysosomal degradation. Our detailed examination on the step of autophagy that is inhibited by HCQ@ZnS@exo and HCQ@ZnS@exo@iRGD revealed that this compound blocks autophagosome-lysosome fusion and not degradation capacity of lysosomes as previously assumed.…”
Section: Discussionmentioning
confidence: 99%
“…The release of EVs containing SNCA (alpha-synuclein) was facilitated by the inhibition of the autophagy-lysosome pathway in human neuroglioma cells, and transmission electron microscopy (TEM) confirmed that amphisomes served as novel secretory organelles in this regulation of cellular homeostasis [119,120]. Notably, mechanical stress can induce autophagy component release via sEVs through the amphisome pathway [38]. More importantly, Jeppesen et al confirmed that active secretion of cytosolic DNA occurs through an amphisome-dependent mechanism in DKO-1 cells [13].…”
Section: The Crosstalk Between Mvbs and Autophagymentioning
confidence: 96%
“…Furthermore, pyruvate kinase type M2 and histamine can promote the fusion of MVBs with the plasma membrane via the phosphorylation of SNAP23 at serine 95 or serine 110 in tumor cells, respectively [14,15]. Notably, the process of MVB docking and fusion in various cell types is induced by Ca 2 + , which may play a role in the activation of functional Rab and SNARE proteins (see above) [38,89,93]. Remarkably, HSP90 can also directly interact with and deform membranes via a conserved amphipathic helix, which suggests that its unique membrane-deforming function may provide the driving force for the fusion of the plasma membrane and MVBs and thus the release of exosomes [104].…”
Section: Fusion Of Mvbs With the Plasma Membranementioning
confidence: 99%
See 1 more Smart Citation